2023
DOI: 10.46827/ejes.v10i1.4642
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Higher Education Partnerships in the Covid-19 Era; Students’ Rating of an Online and Modular Learning Programme

Abstract: Transnational educational partnerships among tertiary institutions have been around for a long time all over the world. There will always be cases where some institutions or countries have a better capacity and operational advantage over others. It is because of this rationale that educational institutions from two or more countries through collaborative partnerships and or relationships, rally or agree to counter contemporary challenges in their countries and they have been very successful in this for a long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Este estudio coincide con el de (Graefen y Fazal, 2023), el cual investigó sobre esta problemática y los resultados encontrados establece que Instagram es útil como plataforma para que los estudiantes formen círculos sociales pequeños o grandes en los que se apoyen mutuamente abordando sus necesidades educativas, colaborando mutuamente con tareas designadas y participando en sesiones de estudio y cuestionarios.…”
Section: Figuraunclassified
“…Este estudio coincide con el de (Graefen y Fazal, 2023), el cual investigó sobre esta problemática y los resultados encontrados establece que Instagram es útil como plataforma para que los estudiantes formen círculos sociales pequeños o grandes en los que se apoyen mutuamente abordando sus necesidades educativas, colaborando mutuamente con tareas designadas y participando en sesiones de estudio y cuestionarios.…”
Section: Figuraunclassified
“…Instagram is a social networking website where users may share photos and videos. It is owned by Meta Platforms, an American corporation (10). Currently, there are 1.35 billion monthly active users of Instagram, making up 17.6% of the total population.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic books, frequently referred to as digital books, have been established as a feasible alternative among these improvements since the end of the 1990s. About every college and university all over the world reported that online learning had replaced traditional classroom instruction because of COVID-19 (Graefen & Fazal, 2023). As substitutes and additions to traditional printed materials, digital textbooks, e-books, online resources, and multimedia tools have been developed (Simon & Garcia-Belmar, 2016).…”
Section: Introductionmentioning
confidence: 99%